A preliminary study of dengue infection in Brunei - Osman, Osmali; Fong, Mun Yik; Devi, Shamala (Institute of Infectious Diseases, 2007)
The purpose of this study was to examine the extent of dengue infection in Brunei and to determine the predominant serotype circulating in the country. The study generated useful epidemiological data on dengue infection in Brunei. A total of 271 samples from patients suspected of having dengue infections were selected and analyzed. All patients were seen in clinics and hospitals in Brunei. The samples were collected from April 2005 to April 2006 and transported to the WHO Collaborating Centre for Arbovirus Reference and Research, University of Malaya, Malaysia. The following tests were used to achieve the objectives: in-house IgM-capture enzyme-linked immunosorbent assay, virus isolation in mosquito albopictus cell line (C6/36), and viral RNA detection and serotyping by reverse transcriptase-polymerase chain reaction (RT-PCR). The results show that 45 people were positive for dengue-specific IgM (27 males and 18 females), while RT-PCR detected dengue viral RNA in 12 patients, 3 identified as DEN-1 and 9 as DEN-2. Dengue virus was isolated from 6 patients using the C6/36 cell line; 3 were DEN-2 isolates and 3 were DEN-1 isolates. These data show that dengue virus is circulating in Brunei and the predominant infecting serotype for that period was DEN-2 followed by DEN-1. This study is the first to report the detection and isolation of dengue virus from Brunei using RT-PCR and culture in the C6/36 albopictus mosquito cell line.